PENGEMBANGAN MODIFIKASI MEDIA PERMAINAN SPIN PADA MATERI SEPAKBOLA - Santosa, Agus; Sonjaya, Fauzan Ali (STKIP Pasundan, 2019)
The purpose of this study was to create a football learning model product in the form of a spin game modification. The research method used is a qualitative approach. The population used was the fifth grade students of SD Negeri Bojongwaru 02, Pameungpeuk Subdistrict, Bandung Regency with a total of 22 students, then 12 students were selected as samples after going through a simple random sampling technique. The results of data analysis and expert evaluation of learning, obtained an average rating of 84% which means having good criteria, then the results of data analysis from Penjas experts, obtained an average rating of 90% which means having good criteria. The results of the analysis of small-scale trial data obtained the corresponding percentage of answer choices 82.2% which means having good criteria, and the results of large-scale trial data analysis obtained a percentage of 90.5% which means it has very good criteria. Based on the findings above, the implications of these findings are: 1) Teachers are recommended to use a lot of spin media modification games, 2) Students are expected to be able to develop interests and talents in learning activities in schools, 3) It is hoped that further research will be more in-depth.